Direct predictive speed control of permanent magnet synchronous motor fed by matrix converter - Najmeh Movahhed Neya; Sajad Saberi; Babak Mozafari (International Journal of Power Electronics and Drive Systems (IJPEDS), 2020)
This paper proposes a non-cascade -single loop- Direct Speed Control algorithm for surface mounted Permanent Magnet Synchronous Motor (PMSM) fed by Matrix Converter. The proposed method uses Finite Control Set Model Predictive Control (FCS-MPC) to manipulate system speed and currents simultaneously. Also, for better performance of the predictive method, an observer designed to estimate mechanical torque and other uncertain parameters of the mechanical subsystem as a lumped disturbance. Simulation results using Matlab/Simulink demonstrate the performance of proposed algorithm.